2011
DOI: 10.1016/j.bpj.2011.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Interleaflet Coupling and Domain Registry in Phase-Separated Lipid Bilayers

Abstract: There is clear evidence of an interleaflet coupling in model lipid/cholesterol membranes exhibiting liquid-liquid phase separation. The strength of this coupling is quantified by the mismatch free energy, γ. We calculate it using a molecular mean-field model of a phase-separated lipid/cholesterol bilayer and obtain values that increase as the concentration of saturated lipids in the coexisting phases is increased. These values lie in the range 0.01-0.03 k(B)T/nm(2). We clarify the relationship between the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
64
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 31 publications
8
64
2
Order By: Relevance
“…Thus, daptomycin has a dramatic effect on the liquid-order/disorder balance of the cell membrane. Several studies have shown that there is a coupling between the bilayer leaflets and that local disorder in one leaflet stimulates local disorder of the opposite leaflet (52)(53)(54). Thus, the distortion of lipids in the outer leaflet by daptomycin likely attracts fluid lipids in the inner leaflet as well.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, daptomycin has a dramatic effect on the liquid-order/disorder balance of the cell membrane. Several studies have shown that there is a coupling between the bilayer leaflets and that local disorder in one leaflet stimulates local disorder of the opposite leaflet (52)(53)(54). Thus, the distortion of lipids in the outer leaflet by daptomycin likely attracts fluid lipids in the inner leaflet as well.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mean-field approach of Putzel et al (12), on the other hand, yields explicit predictions for the contributions of gauche bond energy, configurational entropy, and orientational interactions to L mol for flat membranes. Combining the results from these two complementary approaches should thus yield a predictive expression of the total interleaflet coupling, L ¼ L mol þ L fluct , which incorporates both molecular-scale and collective fluctuation effects.…”
Section: Discussionmentioning
confidence: 99%
“…Although the renormalization of the bending rigidity should only lead to small changes in L fluct (this is because k 0 À k R ( 3k B T ( k 0 for l(100 mm), the temperature dependence of k R for both the domain and background phases may offer a means to extract ' from experiments that quantify vesicle shape fluctuations (36)-and thus k R -over a range of temperatures. From a simulation perspective, on the other hand, the theoretical predictions presented in this article are amenable to verification via particle-based simulations of membrane systems, in which the elastic properties between the domains and the matrix phase are explicitly tuned, ' is extracted from simulated membrane undulation spectra (24), and L is measured from, e.g., out-of-alignment fluctuations (10,12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations